GERAKAN LITERASI KEUANGAN MELALUI MEDIA MENABUNG SEJAK DINI - Desmy Riani; Wika Ajmilah; Nuru Falma; Yuggo Afrianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
This study aims to explain how the financial literacy movement can be implemented through the media of saving from an early age, especially among TPQ AL-Bana children in Bojongnangka Village, Gunung Putri District. When we teach there, we see that the children at TPQ Al-Bana still need intensive socialization about the importance of saving so that a culture of saving grows from an early age. Therefore, we took the initiative to hold a financial literacy movement through the media of saving. The research method used was that the proposing team carried out a field survey and looked at the conditions and problems faced by partners, the review stage and the alternative program planning stage. The result is that with the quiz we know that children understand how important it is to save because saving is very beneficial and with a piggy bank they will be motivated to learn to save.